Structural phase transitions in [(CH3)4P]3M2Cl9 (M = Bi and Sb) hybrid compounds revealed by temperature-controlled Raman spectroscopy and X-ray diffraction. (May 2023) - Khalfa, M.; Oueslati, A.; Khirouni, K.; Gargouri, M.; Rousseau, A.; Bardeau, J.-F.; Corbel, G.
Abstract: Two phosphonium chlorobismuthate (III) and chloroantimonate (III) crystals have been prepared and their thermal behaviors have been studied by thermal analyses, temperature-controlled Raman spectroscopy and temperature-controlled X-ray diffraction. Refinements of the diffraction pattern, carried out by the Le Bail method, confirm the high purity of both samples. Raman spectroscopy revealed a decomposition of the compounds above 250 °C, later confirmed by energy dispersive X-ray (EDX) analysis and X-ray powder diffraction (XRPD). In addition, temperature-controlled Raman spectroscopy and X-ray powder diffraction allowed us to reveal the existence of transitions in the 25–150 °C temperature range, which had previously gone completely unnoticed despite numerous published studies. These transitions are related to reorientations of the tetramethyl phosphonium cations [(CH3 )4 P] + and rotations of [M2 Cl9 ] 3- (M = Bi or Sb) dimers in the structure. The rearrangements of the cationic and anionic entities then change the thermal expansion coefficients measured by diffraction along the trigonal crystallographic axes of the structure. Highlights: [(CH3 )4 P]3 Bi2 Cl9 (PCB) and [(CH3 )4 P]3 Sb2 Cl9 (PCA)compounds have been synthesized by slow evaporation method. Raman and XRD studies reveal that the crystalline structure starts to decompose above 250 °C. Phase transitions are due to organic [(CH3 )4 P] + cations' reorientation with a rotation of [M2 Cl9 ] 3− anions (M = Bi or Sb). New phase transitions of second order type were detected by Raman spectroscopy and X ray diffraction.